Dynamic changes in root hydraulic properties in response to nitrate availability - Gloser, Vít; Zwieniecki, Maciej A; Orians, Colin M; Holbrook, N Michele (Journal of experimental botany, 2007)
Changes in root hydraulic resistance in response to alterations in nitrate supply were explored in detail as a potential mechanism that allows plants to respond rapidly to changes in their environment. Sunflower (Helianthus annuus cv. Holiday) plants grown hydroponically with limited nitrate availability (200 micromol l(-1)) served as our model system. Experimental plants were 6-9-weeks-old with total dry mass of 2-4 g. Root pressurization of intact plants and detached root systems was used to elucidate the temporal dynamics of root hydraulic properties in sunflower plants following changes in external nitrate availability. The response was rapid, with a 20% decrease in hydraulic resistance occurring within the first hour after the addition of 5 mM nitrate and the magnitude of the effect was dependent on nitrate concentration. The change in root hydraulic resistance was largely reversible, although the temporal dynamics of the response to nitrate addition versus nitrate withdrawal was not symmetric (a gradual decrease in resistance versus its fast increase), raising the possibility that the underlying mechanisms may also differ. Evidence is presented that the observed changes in root hydraulic properties require the assimilation of nitrate by root cells. The hydraulic resistance of roots, previously stimulated by the addition of nitrate, increased more than in control plants in low nitrate under anoxia and that suggests a key role of aquaporin activity in this response. It is proposed that a rapid decrease in root hydraulic resistance in the presence of increased nitrate availability is an important trait that could enhance a plant's ability to compete for nitrate in the soil.
Keywords: rostlinné proteiny; Plant Proteins; voda; Helianthus; Nitrates; Water; Adaptation, Physiological; dusičnany; Plant Roots; kořeny rostlin; fyziologická adaptace; Aquaporins; akvaporiny